Perbedaan Higher Order Thinking Skills pada Model Problem Based Learning dan Model Konvensional - Rizky Tyas Aria Kurniasari; Supriyono Koeshandayanto; Sa’dun Akbar (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Thematic learning carried out in elementary schools has not trained students' high-level thinking skills as a whole due to the use of learning models that tend to be monotonous and make students bored. This study aims to determine the effect of the Problem Based Learning (PBL) model on HOTS (Higher Order Thinking Skillls). The research method used is quantitative experiments with the design of nonequivalent group design. The results showed that the teacher's implementation was sufficient in accordance with the syntax of the PBL learning model so that it could influence HOTS students. The difference in HOTS scores between the two classes is indicated by the average post-test scores. The use of PBL models should be implemented for students to be able to train HOTS students.Abstrak: Pembelajaran tematik yang dilaksanakan di SD belum melatihkan kemampuan berpikir tingkat tinggi siswa secara keseluruhan dikarenakan penggunaan model pembelajaran yang cenderung monoton dan membuat siswa jenuh. Penelitian ini bertujuan untuk mengetahui pengaruh model Problem Based Learning terhadap Higher Order Thinking Skillls. Metode penelitian yang digunakan yaitu kuantitatif eksperimen dengan desain nonequivalent group design. Hasil penelitian menunjukan bahwa keterlaksanaan guru sudah cukup sesuai dengan sintaks model pembelajaran PBL sehingga dapat berpengaruh terhadap HOTS siswa. Perbedaan skor HOTS antara dua kelas ditunjukkan oleh rata-rata nilai post-test. Penggunaan model PBL hendaknya dapat diimplementasikan kepada siswa agar dapat melatih HOTS siswa.